The transition to a low carbon system and the role of incumbent companies and public policy - Salavisa, I.; Sousa, C. (24th EAEPE Conference, Economic Policy in Times of Crisis, 2012)
The aim of this paper is to analyse the role of the historical monopolistic electrical power company in the transition to a new energy paradigm in Portugal in light of the new regulatory framework.